KETEPATAN PENGGUNAAN SIMBOL DAN SINGKATAN PADA FORMULIR IGD RUMAH SAKIT PKU MUHAMMADIYAH GAMPING - Nisa Rahmawati; Harinto Nur Seha; Rina Yulida (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
The provision medical records quality cannot be separated from consistent recording in the use of medical symbols and abbreviations.. Symbols and abbreviations have been regulated in SNARS Edition 1.1. The uniform use of medical symbols and abbreviations aims to make the writing of terms understandable and can be used as a communication tool between health workers. Hospitals must have regulations, regarding the symbols and abbreviations used. Based on the results of preliminary studies at PKU Muhammadiyah Gamping Hospital, monitoring and evaluation have never been carried out regarding the use of symbols and abbreviations. Research on the accuracy of the use of symbols and abbreviations has also never been done, so it is necessary to conduct a review of the problem. This study used descriptive observational method with quantitative approach and cross sectional design. A purposive sampling technique used to 100 samples on the emergency room form for inpatients in the first quarter of 2022. The results showed that there was no monitoring and evaluation related to the use of symbols and abbreviations at PKU Muhammadiyah Gamping Hospital. The percentage of correct use of symbols was 27% and the percentage of correct use of abbreviations was 37%. The results of the analysis show that the inaccurate use of medical symbols and abbreviations is caused by the lack of socialization to related health workers, and there is non-compliance with officers in using medical symbols and abbreviations that have been regulated in the applicable guidelines at PKU Muhammadiyah Gamping Hospital.